Biofortified sweet potatoes as a tool to combat vitamin A deficiency: Effect of food processing in carotenoid content - Severo, Joseana; Santos, Felipe Nardo dos; Samborski, Tarcísio; Rodrigues, Rosane; Mello, Alexandre Furtado Silveira (Sociedad Chilena de Nutrición, Bromatología y Toxicología, 2021)
The supply of food products that present adequate nutritional quality is extremely important for maintaining the health of the population. Thus, different techniques have been used to obtain biofortified foods, with the aim of combating malnutrition caused by the absence of essential micronutrients, especially in the poorest populations. This review presents an overview of biofortification, with an emphasis on orange-flesh sweet potatoes (OFSP), and points out the effects of food processing on nutritional compounds. The identification of cultivars and biofortification actions to obtain biofortified OFSP by conventional breeding are presented as affordable strategies to supply β-carotene to alleviate vitamin A deficiency, without having ethical dilemmas related to transgenics. Studies using OFSP have shown promising results in obtaining foods with high levels of carotenoids. However, biofortified species must be validated for crop production viability, target micronutrient bioavailability and bioaccessibility, as well as the effect of processing on nutrients, so that the benefits to human health are effectively achieved.